Implementing Computational Thinking-Based Summative Assessment in STEM: Opportunities and Barriers in an Indonesian Islamic Senior High School - Winarni, Sri; Driana, Elin; Ernawati, Ernawati; Setiadi, Hari (FKIP Universitas Lampung, 2025)
Rapid technological advancement and the increasing complexity of real-world problems require students to develop ways of thinking that enable them to analyze, structure, and solve problems systematically. Computational thinking (CT) has therefore emerged as a crucial competence, particularly within STEM education. Despite growing interest in CT integration through project-based learning, limited attention has been given to how CT is incorporated into end-of-schooling summative assessment at the senior high school level. This study examines teachers’ and students’ understanding of computational thinking, their perceptions of CT-based summative assessment through STEM projects, classroom implementation practices, and the challenges faced during implementation. Using a qualitative case study approach, data were collected through interviews, classroom observations, and document analysis at a private Islamic senior high school in Indonesia. The participants included seven teachers from different subject areas and eleven twelfth-grade students who were directly involved in a CT-based summative STEM project. Data were analyzed thematically through an iterative process of data condensation, display, and verification. The findings indicate that both teachers and students generally conceptualize CT as systematic, step-by-step problem-solving. While teachers demonstrate a broader conceptual understanding of CT, its core dimensions, such as decomposition, abstraction, and algorithmic thinking, are not yet explicitly operationalized in summative assessment criteria. Students can apply CT to practical project tasks, although their understanding remains basic. Both teachers and students perceive CT-based summative assessment positively, as it emphasizes thinking processes, hands-on learning, collaboration, and real-world problem contexts. However, implementation is constrained by limited assessment literacy, challenges in interdisciplinary alignment, time constraints, unequal student participation, and resource limitations. Overall, the study suggests that CT-based summative assessment through STEM projects has strong potential to support meaningful learning at the senior high school level. Nevertheless, clearer assessment frameworks, targeted teacher professional development, and stronger institutional support are required to bridge the gap between conceptual intentions and assessment practices. Keywords: computational thinking, project-based learning, summative assessment, STEM, 21st-century competencies.